2020
DOI: 10.1371/journal.pntd.0007966
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as an adjuvant to anti-epileptic treatment in persons with onchocerciasis-associated epilepsy: A randomized proof-of-concept clinical trial

Abstract: Introduction Recent findings from onchocerciasis-endemic foci uphold that increasing ivermectin coverage reduces the epilepsy incidence, and anecdotal evidence suggests seizure frequency reduction in persons with onchocerciasis-associated epilepsy, when treated with ivermectin. We conducted a randomized clinical trial to assess whether ivermectin treatment decreases seizure frequency. Methods A proof-of-concept randomized clinical trial was conducted in the Logo health zone in the Ituri province, Democratic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…There is anecdotal evidence that ivermectin in O. volvulus infected PWE may decrease the frequency of seizures [27]. Moreover, a recent randomised clinical trial in DRC showed that O. volvulus infected PWE who received multiple doses of ivermectin were more likely to be seizure-free during the last four months of a one year trial than O. volvulus PWE who received only one dose of ivermectin [28]. The small sample size of our study and the low mf density at baseline, most likely explains why a bene cial effect of ivermectin was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…There is anecdotal evidence that ivermectin in O. volvulus infected PWE may decrease the frequency of seizures [27]. Moreover, a recent randomised clinical trial in DRC showed that O. volvulus infected PWE who received multiple doses of ivermectin were more likely to be seizure-free during the last four months of a one year trial than O. volvulus PWE who received only one dose of ivermectin [28]. The small sample size of our study and the low mf density at baseline, most likely explains why a bene cial effect of ivermectin was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In Mahenge, Ulanga district, Tanzania [ 10 , 11 ], CDTI had been implemented for more than 20 years, Kitgum and Pader districts, Uganda [ 5 ], CDTI had been implemented since 2009, and in Cameroon, in Bilomo (Mbam valley), mass drug administration of ivermectin was implemented in 1998 and around mid-1990s in Kelleng (Sanaga valley) [ 12 ]. Other PWE were enrolled during the screening of PWE for participation in a clinical trial to investigate the effect of ivermectin on the frequency of seizures in persons with O. volvulus infection in the Logo health zone, Ituri province, Democratic Republic of Congo (DRC) [ 13 ]. In the Logo health zone, CDTI had never been implemented [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…A multiple logistic regression analysis showed a borderline insignificant association at 5% significance level between ivermectin treatment and being seizure-free at month 4 (OR: 1.652, 95% CI 0.975-2.799; p = 0.062) [9]. Given the small sample size, the results of the trial were difficult to interpret [9]. During the trial, we realized that the planned sample size (110 individuals) could not be reached as the inclusion criteria were very strict.…”
Section: Introductionmentioning
confidence: 92%
“…Ninety-four of them who met the criteria for onchocerciasis-associated epilepsy (OAE) [8], and who experienced at least two seizures per month by the time of assessment, were enrolled in a four-month proof-of-concept trial. A multiple logistic regression analysis showed a borderline insignificant association at 5% significance level between ivermectin treatment and being seizure-free at month 4 (OR: 1.652, 95% CI 0.975-2.799; p = 0.062) [9]. Given the small sample size, the results of the trial were difficult to interpret [9].…”
Section: Introductionmentioning
confidence: 98%